Influencia de los ámbitos familiar, educacional y mediático en la adopción de identidades por los niños y las niñas a través de sus dibujos - Maeso Broncano, Ana (Arte, Individuo y Sociedad, 2008)
The following approach involves children drawing somebody they would like to be alike. In this sense, there would be a better determination of the role models children identify with. The aim of this approach is knowing to what extent does family, education and mass media influence children. As both emotional and rational involvement is greater with direct contact, being related to family in the first place, the fact that role models chosen by children will be related to family becomes a clear hypothesis. The percentage of drawings related to mass media characters would be much greater, and depicted characters will then belong to most popular media manifestations. This shows the influence of mass media on early ages, as well as the development of taste uniformity.